2014
DOI: 10.1111/1469-0691.12364
|View full text |Cite
|
Sign up to set email alerts
|

Added value of multiplex Luminex Gastrointestinal Pathogen Panel (xTAG® GPP) testing in the diagnosis of infectious gastroenteritis.

Abstract: The Luminex Gastrointestinal Pathogen Panel (xTAG(®) GPP) detects in one assay the most common gastroenteritis-causing pathogens and toxins, namely adenovirus 40/41, norovirus genogroup (NG) I/II, rotavirus A, Clostridium difficile toxin A/B, Campylobacter sp., Escherichia coli O157, Enterotoxigenic E. coli heat-labile enterotoxin/heat-stable enterotoxin, Salmonella sp., Shiga-toxin producing E. coli, Shiga-like toxin (Stx)1/2, Shigella sp., Vibrio cholerae, Yersinia enterocolitica, Cryptosporidium sp., Entamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 18 publications
3
71
1
Order By: Relevance
“…11,12,[20][21][22][23]25,[29][30][31][32][33][34]38,39 However, only four studies reported outcomes of verification by pathogen. 20,23,25,30 Study design Table 7 characterises the design heterogeneity among the studies reported, which should be noted when considering the pooled study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,12,[20][21][22][23]25,[29][30][31][32][33][34]38,39 However, only four studies reported outcomes of verification by pathogen. 20,23,25,30 Study design Table 7 characterises the design heterogeneity among the studies reported, which should be noted when considering the pooled study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 19,22,26,27,29,35,39 reported the setting sufficiently to allow judgement on the origin of the infection (hospital vs. community). The majority of studies 11,12,20,21,[23][24][25]28,[30][31][32][33][34][36][37][38] reported recruitment of hospitalised patients, for which a mixed population should be assumed (in terms of origin of infection) as it is unclear at what point in time during hospitalisation each infection occurred. Only one study was identified as a community study, set in Côte d'Ivoire.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Luminex xTAG GPP is the first commercially available assay able to simultaneously detect viruses, bacteria, and parasites on total nucleic acid isolated from a single stool specimen [18]. The present study represents the first application of xTAG GPP to human stool samples collected in Côte d'Ivoire.…”
Section: Discussionmentioning
confidence: 98%